2003
DOI: 10.1021/ar020127o
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotyrosyl Mimetics in the Development of Signal Transduction Inhibitors

Abstract: Phosphotyrosyl (pTyr) residues play important roles in cellular signal transduction by facilitating recognition and binding necessary for critical protein-protein interactions, and for this reason pTyr motifs represent attractive starting points in the development of signaling antagonists. Although the pTyr phosphoryl moiety is central in these phenomena, its incorporation into signaling inhibitors is contraindicated due to enzymatic lability and limited bioavailability associated with phosphate esters. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
71
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 82 publications
0
71
0
Order By: Relevance
“…The potency of DFMP as a PTP pharmacophore has been extensively analyzed (9,15,29,30). Burke et al (9) and Burke and Lee (29) have shown that the DFMP group contributes to high PTP binding affinity.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…The potency of DFMP as a PTP pharmacophore has been extensively analyzed (9,15,29,30). Burke et al (9) and Burke and Lee (29) have shown that the DFMP group contributes to high PTP binding affinity.…”
Section: Tablementioning
confidence: 99%
“…Burke et al (9) and Burke and Lee (29) have shown that the DFMP group contributes to high PTP binding affinity. Its use in the phosphonodifluoromethyl-phenylalanine peptide inhibitors demonstrated that the difluoro group can increase PTP binding by 1000-fold relative to the monofluorinated counterpart (9,29).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…In the previous studies, one of the directions in designing the inhibitors has focused on the synthesis of enzymatically stable phosphotyrosine mimics (pTyr) which contain the fragments of (phosphonomethyl)phenylalanine (Pmp) 1a and its fluoro-substituted analogues 1b, c [3][4][5][6]. However, there is a limitation in the development of the low molecular PTP inhibitors due to several problems including the selectivity and cell permeability.…”
mentioning
confidence: 99%